2020
DOI: 10.58397/ashkmdc.v25i2.319
|View full text |Cite
|
Sign up to set email alerts
|

Awareness Regarding Family Planning Methods Among Final Year Medical Students

Abstract: A cross-sectional awareness survey was conducted among final year MBBS students of ISRA University, Hyderabad from May 2017 to November 2017. After checking eligibility and taking verbal informed consent, 100 participants were included in the study and interviewed using a self-administered questionnaire.Data was analyzed on Statistical Package for Social Sciences version 21. The study results showed that 29 (29%) of the study participants got information about family planning methods from health care providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Two studies assessed sexual and reproductive health education from all years in medical school through surveys of faculty with knowledge of the curriculum 7,53 . Six studies assessed fifth and/or sixth year students about sexual and reproductive health education 34,37,41,50,51,54 . Two studies compared second‐year and fourth‐year students to better understand the differences between the sexual and reproductive health teaching in the preclinical and clinical curricula 39,56 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies assessed sexual and reproductive health education from all years in medical school through surveys of faculty with knowledge of the curriculum 7,53 . Six studies assessed fifth and/or sixth year students about sexual and reproductive health education 34,37,41,50,51,54 . Two studies compared second‐year and fourth‐year students to better understand the differences between the sexual and reproductive health teaching in the preclinical and clinical curricula 39,56 …”
Section: Resultsmentioning
confidence: 99%
“…Most articles assessed medical schools in the United States of America (USA) 2–33 . Additional studies reported sexual and reproductive health education from around the world including Angola, 34 Australia, 35–37 Canada, 38–40 China, 41 the Democratic Republic of Congo, 42 India, 43–45 Iran, 46 Nepal, 47 the Netherlands, 48 Pakistan, 49,50 Turkey, 51 and the United Kingdom 52–54 . Our review largely revealed studies at single medical schools.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations